KAJIAN VARIASI JARAK ANTAR PENGHALANG SUARA YANG DIHASILKAN OLEH SUMBER SUARA - Jumingin, Jumingin (Universitas Islam Negeri Raden Fatah, 2012)
Noise is sound exessive, unwanted and often called the “invisible pollution” that causes phisical effects and pychologica1 effects. Physical effects assodated with the transmision of sound waves through the air, while the pychological effects associated with the human response to sound The purpose of this research is to study variations in the distance between the bariier to the sound produced by the sound source. The method used is an experimental method, which is taking data directly form the field. Retrival of data nouse using a Sound Level Meter, The results show that the distance of 0.5 cm between the barrier can reduce noise by 5.04%, 1 cm distance between the banier can reduce noise by 3.22%, and 2 cm distance between the barrier can reduce noise by 1.36%. It can be concluded that to reduce the sound coming out, can be done by varying the distance between the baniers